2020
DOI: 10.1111/jphd.12384
|View full text |Cite
|
Sign up to set email alerts
|

Blood levels of lead and dental caries in permanent teeth

Abstract: Objectives: The purpose of this study was to determine whether there is an association between lead exposure within the ages of 1-4 years and dental caries in the permanent dentition between ages 9-17 among Mexican youth. Methods: Data were collected for the Early Life Exposures in Mexico to Environmental Toxicants (ELEMENT) cohort from a group of 490 children born and reared in Mexico City. Among ages 1-4 years, blood lead levels were measured in micrograms of lead per deciliter of blood (μg/dL) and the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Eleven studies [16‒19, 21, 24‒29] measured the blood lead (PbB) level through either whole blood or plasma. Two studies [26, 30] measured salivary lead (PbSa) level using unstimulated whole saliva samples.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eleven studies [16‒19, 21, 24‒29] measured the blood lead (PbB) level through either whole blood or plasma. Two studies [26, 30] measured salivary lead (PbSa) level using unstimulated whole saliva samples.…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies were identified for this review, comprising a total of 35,743 participants. Four studies were cohort studies [16][17][18][19], while the remainder were crosssectional [20][21][22][23][24][25][26][27][28][29][30]. The studies were conducted in various countries, including the USA [16,17,21,[25][26][27][28] (n = 7), Brazil [23] (n = 1), Canada [31] (n = 1), Mexico [18,19] (n = 2), Serbia [20] (n = 1), South Korea [24] (n = 1), Spain [22] (n = 1), Thailand [29,30] (n = 2).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations